2018
DOI: 10.1155/2018/4635647
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Serological, and Molecular Observations from a Case Series Study during the Asian Lineage Zika Virus Outbreak in Grenada during 2016

Abstract: This paper describes the spatial and temporal distribution of cases, demographic characteristics of patients, and clinical manifestations of Zika virus (ZIKV) during the 2016 outbreak in Grenada. The first reported case was recorded in St. Andrew Parish in April, and the last reported case was seen in November, with peak transmission occurring in the last week of June, based on test results. Data were collected from a total of 514 patients, of whom 207 (40%) tested positive for ZIKV. No evidence was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…9 In the current study, we prospectively tracked neurodevelopment in a large cohort of ZIKV exposed and unexposed children who were born during a period of active ZIKV transmission in Grenada, Carriacou and Petite Martinique. 10 We conducted the INTERGROWTH-21st Neurodevelopment Assessment (INTER-NDA), 11 Cardiff…”
Section: Introductionmentioning
confidence: 99%
“…9 In the current study, we prospectively tracked neurodevelopment in a large cohort of ZIKV exposed and unexposed children who were born during a period of active ZIKV transmission in Grenada, Carriacou and Petite Martinique. 10 We conducted the INTERGROWTH-21st Neurodevelopment Assessment (INTER-NDA), 11 Cardiff…”
Section: Introductionmentioning
confidence: 99%
“…In this review, there was epidemiologic data supporting an association between adult ZIKV infections and neurological complications, namely GBS, given the mirroring of the trends of these two diseases [32,35,43,49,70,121]. After excluding studies that intentionally enriched for patients with neurological complications, we calculated a risk of neurological sequelae in ZIKV infection of 0.3%.…”
Section: Discussionmentioning
confidence: 99%
“…There were also children in this study from range of one day old to 90 years old (age range). [70] g Daudens-Vaysse et al reported on 9077 suspected cases in the French Territories of America and 7,600 of these were from Martinique; 58 from Saint-Martin, 1,030 from French Guiana, and 389 from Guadeloupe. Total confirmed among the territories was 249 cases.…”
Section: Zikv Case Definitionsmentioning
confidence: 99%
“…In 2016, the tri-island nation of Grenada, Carriacou, and Petit Martinique experienced a ZIKV outbreak with peak transmission from May through October of 2016 [ 13 ]. In April 2016, the Ministry of Health and the Windward Islands Education and Research Foundation (WINDREF) began recruiting pregnant women for participation in a ZIKV surveillance study during their antenatal and postnatal care appointments at local health centers, regardless of whether they presented with ZIKV symptoms.…”
Section: Introductionmentioning
confidence: 99%